Evaluating flexibility notions in mass housing of North Cyprus through learning from her rural vernacular architecture - Gilani, Golshid (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: One of the most important considerations in housing design is flexibility that refers to the idea of accommodating change over time. This concept is covered by the recent architecture, although it was used since the past times. In fact, flexibility is one of the most significant principles of traditional dwellings. Hence, it is also observed in rural vernacular architecture of North Cyprus as well. But it seems that, unlike vernacular architecture, flexibility is not considered as an axiom in recent architecture of North Cyprus especially in “build and sell” type of housing projects, which can be regarded as the subset of mass housing. In this study, the main purpose is to evaluate notions of flexibility in recent “build and sell” type of housing projects of North Cyprus through learning from her rural vernacular architecture. To achieve this aim, first the criteria for evaluating flexibility are going to be extracted through reviewing the literature. Then, notions of flexibility in rural vernacular architecture of North Cyprus are investigated based on the criteria, which were derived from the theoretical background. After that, particular case studies from recent “build and sell” type of housing projects of North Cyprus are going to be evaluated in terms of flexibility, to indicate if they have enough potential for flexibility or not; and if the houses can be adapted to various users and their changing needs and wishes. Finally, some recommendations are proposed for improving flexibility in recent “build and sell” type of housing projects of North Cyprus through applying notions of flexibility of her vernacular architecture. The data collection method is based on observations in the forms of photographs, maps, AutoCAD drawings including; plans, sections, elevations and site plans as well as in situ observations and questionnaire surveys. In general, this study attempts to improve flexibility in recent mass housing design in North Cyprus to provide long-term and short-term flexibility of housing through learning from her vernacular architecture, in order to give different users possibility of taking control of their living environments. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Konut tasarımında en önemli faktörlerden birisi değişen zaman içerisinde değişimi barındıran esnekliktir. Bu kavram önceki dönemlerden bu yana kullanılmasına rağmen, çağdaş mimarlık içinde yer alır. Aslında esneklik geleneksel konutların en önemli prensiplerindendir. Esneklik Kuzey Kıbrıs‟ın kırsal Yöresel mimarisinde de gözlemlenir. Fakat yöresel mimarinin aksine, esneklik Kuzey Kıbrıs‟ın çağdaş mimarisinde, özellikle toplu konut projelerinin alt grubu olan “yap-sat” türü konutlarda, bir aksiyom olarak düşünülmemektedir. Bu çalışmada temel amaç, Kuzey Kıbrıs‟ın yöresel mimarisinde esneklik nosyonlarını araştırmak; bundan çıkarımlar elde etmek; ve çağdaş “yap-sat” türü konut projelerine uygulamaktır. Bu amaca ulaşabilmek için, öncelikle esnekliği değerlendirebilecek ölçütler literatür taramasından çıkarılacaktır. Sonra, Kuzey Kıbrıs‟ın yöresel mimarisindeki esneklik nosyonu bir önceki bölümden elde edilen ölçütlere dayandırılarak incelenmektedir. Bundan sonra, Kuzey Kıbrıs‟tan bazı çağdaş “yap-sat” konut projeleri, esnekliğe uygunlukları yeterince esneklik potansiyellerinin olup olmadığı; çeşitli kullanıcılara ve kullanıcıların değişen gereksinimlerine ve dileklerine adapte olabilmeleri açısından incelenmektedir. Son olarak, Kuzey Kıbrıs‟ın çağdaş “yap-sat” konut projelerinde esnekliğe ulaşabilmek için, yöresel mimarinin esneklik kavramından faydalanmasını sağlayacak bazı öneriler sunulMaktadır. Veri toplama yöntemi fotoğraflar, haritalar, Autocad gizimleri; planlar, kesitler, görünüşler, ve vaziyet planları yanında yerinde yapılan gözlemler ve anketlere dayanmaktadır. Sonuç olarak, bu çalışma hem kısa hem uzun dönemde konut yapımının sürdürülebilirliğini sağlamak amacıyla, geleneksel mimariden dersler çikararak Kuzey Kıbrıs‟ın günümüz toplu konut tasarımındaki esnekliği geliştirmeyi; ve bu sayede kullanıcılara kendi yaşamsal çevrelerinin kontrolünü ele alma olanağını vermeyi amaçlar.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2012. Supervisor: Assoc. Prof. Dr. Özlem Olgaç Türker.
Keywords: Public Housing - Mass Housing - Cyprus, North; Flexibility - Adaptability - Rural Vernacular Architecture of North Cyprus Recent Architecture of North Cyprus - Building and Sell type of Housing